Clinical Symptom Analysis of Characteristic Bacteria Causing Subclinical Mastitis in Dairy Cow at Pengalengan, Bandung Regency - Pranyata Tangguh Waskita; Roostita L Balia; I Made Joni; Wendry Setiyadi Putranto (International Journal Labs, 2024)
Mastitis is an udder infection that affects many dairy farms in Indonesia. Many causes can be identified to see the etiology. This study was conducted to determine the bacteria that causes mastitis and attacks dairy farms in the Bandung Regency Region. Based on the results of isolation and identification by examination of Blood Agar Media (BAP), Catalase Test, Coagulase Test, Gram staining, and DNAse Test of milk samples taken from three farm areas in Warnasari and Babakan Kiara in Pengalengan District and Citawa District Kertasari District, the bacteria that cause mastitis are Staphylococcus aureus COPS and CONS, Staphylococcus pyogenes, Staphylococcus epidermidis, and Staphylococcus saprophytes. The characteristics of Clinical symptoms analysis from the bacteria causing subclinical Mastitis as seen as udder redness, swelling, and fever. There are tissue necrosis in the nipple and part of the udder. The milk parenchyma becomes fribillated, and the milk produced becomes mixed with blood, drips continuously, and appears watery in the presence of flakes, clots, and mucus. Implementation Early, prompt, and accurate diagnostic examinations must be carried out to prevent the occurrence of subclinical mastitis so that the objective can benefit the farmers for the future livelihood of the farm